Differential transcription of CYP52 genes of Yarrowia lipolytica during growth on hydrocarbons - Drennan, Michael Bertram (University of the Free State, 2000)
A large number of monooxygenases contain a haem protein containing cytochrome P450. These moncoxygenases enzymatically catalyze dioxygen activation at the cytochrome P450 haem protein. The cytochrome-P450-dependent monooxygenases are involved in many steps of the biosynthesis and the degradation of compounds such as steroids, fatty acids, prostaglandins, leukotrienes, and n-alkanes. The first enzymatic step of hydrocarbon assimilation is the terminal hydroxylation of the n-alkane by a cytochrome P450 enzyme system. The enzyme system bound to the endoplasmic reticulum (ER), consists of an NADPH-cytochrome P450 reductase involved in transferring electrons (Govindaraj & Poulos, 1997; Nelson & Strobel, 1988), and a cytochrome P450 acting as hydroxylase in a typical monooxygenase reaction. The cytochrome P450 monooxygenase (CYP52) multigene family involved in the terminal hydroxylation of n-alkanes and fatty acids has been characterized in yeast species such as Candida maltosa, Candida tropicolis and Candidaapicola (Lottermoser et al., 1996; Seghezzi et al., 1992; Zirnmer et al., 1.996). These include eight genes in C. maltosa, seven in C. tropicalis. and two In C. apicola. Yarrowia lipolytica, originally classified as a Candida, uses few sugars (mainly glucose) as a carbon source. This yeast readily assimilates organic acids, various polyalcohols, and 'normal parafins. The first of eight Y. lipolytica cytochrome P450 monooxygenase characterized was YIALK 1 (Iida et al., ] 998). Subsequent characterization of the remaining seven Y. lipolytica CYP52 genes showed YIALKl and YIALK2 to be the major P450 forms involved in assimilation of shorter-chain n-alkanes (C10-C16), while the remaining YIALK genes (Y1ALK3 through YIALK8), did not appear to 'be significantly involved in C10-C16 assimilation (Iida et al., 2000). The induction of the eight Y. lipolytica CYP52 genes on longer-chain n-alkanes (C18-C28) and long-chain fatty acids was investigated using gene-specific RT -PCR reactions as well as Northern hybridizations. A PCR-based approach was used to prepare eight gene-specific Y lipolytica CYP52 probes. The probes designed for this study were the same as those used by Iida et al. (2000). Complications that hampered the study included: (i) the insolubility of the very long-chain n-alkanes and fatty acids in water, which necessitated the use of co-solvents such as pristane and Tween 80; (ii) the poor growth of the selected yeast strain under the conditions used by lida et al. (2000) for induction of the genes; (iii) the large number of genes investigated; (iv) the logistical problems associated with comparing a large number of genes under so many growth conditions, and (v) the difficulty in isolating RNA from Y. lipolytica. Induction of the Y. lipolytica CYP52 genes were studied in the presence of glucose, tetradecane, hexadecane, octadecane, mixtures of docosane and pristane, octacosane and pristane, stearic acid and Tween 80 and behenic acid and Tween 80. Negative controls constituted cultures without any substrate as well as cultures containing only either pristane or Tween 80. The first two Y. lipolytica CYP52 genes investigated, YIALK I and YIALK2, showed preferential induction on all the substrates tested. Genes YIALK3 through Y/ALK6 showed relatively weaker induction on the substrates tested when compared to YIALK 1 and YlALK2. No mRNA transcripts were observed for either Y1ALK7 or Y1ALK8 on any of the substrates tested at any of the induction times. These results were not only repeated for both the RT -PCR and Northern hybridization experiments, but were confirmed for the shorter-chain n-alkanes by Iida et al. (2000). Variations in the levels of Y lipolytica CYP52 gene transcripts were observed when using glucose pre-grown or acid pre-grown yeast cells for the induction, experiments. Phylogenetic analysis of the individual Y. lipolytica CYP52 genes suggested that this multigene family evolved and diverged after branching off from the ancestral P450ALK gene. YlALK 1 and 'YIALK2, which were most prominent in the induction studies, grouped together in the phylogenetic analysis. Comparison of the Y. lipolytica CYP52 and peroxisomal β-oxidation MFE2 gene promoter regions revealed oleic acid-response elements involved in activation by fatty acids. Elucidating the transcriptional activating sequences present in the β-oxidation and CYP52 enzyme systems could lead to an understanding of the regulation of enzymes that contribute to the terminal- and β- oxidation reactions occurring within these n-alkane-assimilating yeasts.

'n Groot aantal monooksigenase bevat heemproteïne wat sitochroom P450 bevat. Hierdie morncëksigenase kataliseer dioksigeenaktivering by die sitochroom P450 heemproteïne ensimaties. Die sitochroom-P450-afhanklike ·monobksigenase is betrokke by die vele stappe van biosintese en die afbreking van verbindings soos steroïde, vetsure, prostaglandiene, leukotrieens, en n-alkane. Die eerste ensimatiese stap van koolwaterstofassimilering is die terminale hidroksilering 'van die n-alkane deur 'n sitochroom P450 ensiemstelsel. Die ensiemstelsel wat aan die endoplasmatiese retikulum (ER) verbind is, bestaan uit 'n NADPH-sitochroom P450 reduktase wat by die oordra van elektrone betrokke is (Govindaraj & Poulos, 1997; Nelson & Strobel, 1988), en 'n sitochroom P450 wat as hidroksilase in 'n tipiese monooksigenase reaksie te werk gaan. Die sitochroom P450 monooksigenase (CYP52) .rnultigeenfamilie wat by die terminale hidroksilering van n-alkane en vetsure betrokke is, is gekarakteriseer in gissoorte soos Candida maltosa, Candida tropicalis en Candida apieokt (Lottermoser et al., 1996; Seghezzi et al., 1992; Zimmer et al., 1996). Hierdie bevat agt gene in C. nialtosa, sewe in C. tropicalis, en twee in C. apieokt. Yarrowia lipolytica, oorspronklik geklassifiseer as 'n Candida, gebruik enkele soorte suiker (hoofsaaklik glukose) as 'n koolstofbron. Hierdie gis assimileer maklik organiese sure, verskeie tipes poli-alkohol, en gewone paraffiensoorte. Die eerste van agt Y. lipolytica sitochroom P450 moncëksigenase wat gekarakteriseer is, was YIALK1 (Iida et al., 1998). Daaropvolgende karakterisering van die oorblywende sewe Y. lipolytica CYP52 gene het YIALK1 en YIALK2 aangetoon as die hoofvorme van P450 wat by die assimilering van korter-ketting ,-alkane (C10-C16) betrokke is, terwyl die oorblywende YIALK gene (van YIALK3 tot YIALK8), nie geblyk beduidend betrokkete gewees het nie by C10-C16-assimilering (lida et al.,2000). Die indusering van die agt Y. lipolytica CYP52 gene op langer-ketting n-alkane (C18-C28) en langketting vetsure is ondersoek deur die gebruik van geen-spesifieke RT-PCR reaksies asook Northern hibridiserings. 'n PCR-gebaseerde benadering is gebruik orn agt geen-spesifieke Y. lipolytica CYP52 ondersoeke voer te berei. Die ondersoeke wat vir hierdie studie ontwerp is, was dieselfde soos wat deur Iida et al. (2000) gebruik is. Komplikasies wat hierdie studie bemoeilik het, het die volgende ingesluit: (i) die onoplosbaarheid van die baie lang-ketting n-alkane en vetsure in water, wat die gebruik van medeoplossers soos pristaan en Tween 80 genoodsaak het; (ii) die swak groei van die geselekteerde gisstam onder die toestande wat deur Iida et al. (2000) vir die indusering van gene gebruik is; (iii) die groot getal gene wat ondersoek is; (iv) die logistiese probleme wat geassosieer word met die vergelyking van 'n groot getal gene onder veelvuldige groeitcetsande, en (v) die moeisaamheid orn RNA van Y. lipolyttca te isoleer. Die indusering van die Y. lipolytica CYP52 gene is bestudeer in die teenwoordigheid van glukose, tetradekaan, heksadekaan. oktadekaan, dokosaan met pristaan, oktakosaan met pristaan, steariensuur met Tween 80 en behensuur met Tween 80. Negatiewe kontrole het kulture saamgestel sonder enige substraat asook kulture wat slegs pristaan of Tween 80 bevat. Die eerste twee Y. lipolytica CYP52 gene wat ondersoek is, nl. YIALK1 en YIALK2, het 'n voorkeurindusering getoon op alle substrate wat getoets is. Gene YIALK3 tot by YIALK6 het 'n relatief-swakker indusering getoon op die substrate wat getoets is wanneer dit met YlALK 1 en YIALK2 vergelyk is. Geen mRNA transkripte is waargeneem hetsy vir YIALK7 of YIALK8 nie of enige van die substrate wat op enige van die induseringstye getoets is nie. Hierdie resultate is nie net vir beide die RT-PCR en Northern hibridiseringseksperimente herhaal nie, maar is vir die korter-ketting n-alkane bevestig deur Iida et al. (2000). Variasies in die vlakke van Y. lipolytica CYP52 geentranskripte is waargeneem wanneer glukose-voorafgekweekte of suurvoorafgekweekte gisselle vir induseringseksperimente gebruik is. Filogenetiese ontleding van die" indiwiduele Y. lipolytica CYP52 gene het daarop gedui dat hierdie multigeenfamilie ontwikkel en uiteengeloop het nadat dit van die voorouerlike P450ALK geen vertak het. YlALKl en YIALK2, wat baie prominent was in die induseringstudies, het saamgegroepeer in die filogenetiese ontleding. Vergelyking van die Y. lipolytica CYP52 en peroksisomale β-oksidasie MFE2 geenbevorderingsgebiede. het olelensuur-responselemente betrokke by die aktivering van vetsure, blootgelê. Die opheldering van die transkripsionele aktiveringsreekse teenwoordig in die β-oksidasie en CYP52 ensiemstelsels, kan lei tot 'n begrip van die regulering van ensieme wat bydra tot die terminaal- en' β-oksidasiereaksies wat binne hierdie ll-alkaanassimileringsgiste plaasvind.
Dissertation (M.Sc. (Microbiology and Biochemistry))--University of the Free State, 2000
Keywords: Hydroxylation; Cytochrome P-450; Cytochrome oxidase; Yeast fungi